Review: shear properties and various mechanical tests in the interface zone of asphalt layers - M. Akraym, Hatim; Muniandy, Ratnasamy; Mohd Jakarni, Fauzan; Hassim, Salihudin (Multidisciplinary Digital Publishing Institute, 2023)
Over four decades, researchers have extensively focused on bonding flexible pavement layers. Scholars have concentrated on the partial or complete lack of interlayer bonding between asphalt layers, which is the primary cause of premature pavement failures, such as cracking, rutting, slippage of wearing courses, and decline in pavement life. These defects are observed within the high horizontal force areas owing to increased speed, braking, and sharp angles when entering or exiting highways and the variations in paving materials, traffic load, and climatic factors. Various studies have investigated the debonding of flexible pavements, and test methods have been developed to find effective solutions. This review is aimed at summarising and discussing certain factors influencing shear strength performance, such as tack coat material, surface characteristics of multi-layer construction of flexible pavements, and different mechanical shear tests. First, bonding in the interface zone area and its Effect on the shear strength performance is reviewed. Subsequently, the types of materials and construction methods and their effects on the bonding quality of the interface zone area are clarified. Finally, the linear relationships between certain effects and the Ability of nanofibers to improve the emulsion properties are discussed. However, no agreement on the optimum tack coat could be obtained owing to the variety of surfaces. Hence, a milling surface is recommended for higher shear strength. The shear test is the most used method for verifying the interlayer bonding strengths, and continuous research endeavours are recommended to analyse debonding in multi-layer asphalt pavements.